2013
DOI: 10.5194/acp-13-6345-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the marine atmospheric boundary layer conditions on VSLS abundances in the eastern tropical and subtropical North Atlantic Ocean

Abstract: Abstract. During the DRIVE~(Diurnal and Regional Variability of Halogen Emissions) ship campaign we investigated the variability of the halogenated very short-lived substances (VSLS) bromoform (CHBr3), dibromomethane (CH2Br2) and methyl iodide (CH3I) in the marine atmospheric boundary layer in the eastern tropical and subtropical North Atlantic Ocean during May/June 2010. The highest VSLS mixing ratios were found near the Mauritanian coast and close to Lisbon (Portugal). With backward trajectories we identifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 40 publications
1
72
1
Order By: Relevance
“…Previous studies have hypothesized that elevated atmospheric mixing ratios of CHBr 3 and CH 2 Br 2 above the Mauritanian upwelling area were mainly of continental origin, since sea-to-air fluxes of these compounds appeared not sufficient to explain the observations (Quack et al, 2007a;Carpenter et al, 2009). In contrast, the investigation by Fuhlbrügge et al (2013) revealed high atmospheric mixing ratios of CH 3 I, CHBr 3 and CH 2 Br 2 close to the coast also in air masses transported from the open ocean, with a significant anticorrelation between the atmospheric mixing ratios and the height of MABL. We therefore examine how oceanic emissions contribute to the mixing ratios of atmospheric halocarbons taking the height of the marine atmospheric boundary layer (MABL) into account.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Previous studies have hypothesized that elevated atmospheric mixing ratios of CHBr 3 and CH 2 Br 2 above the Mauritanian upwelling area were mainly of continental origin, since sea-to-air fluxes of these compounds appeared not sufficient to explain the observations (Quack et al, 2007a;Carpenter et al, 2009). In contrast, the investigation by Fuhlbrügge et al (2013) revealed high atmospheric mixing ratios of CH 3 I, CHBr 3 and CH 2 Br 2 close to the coast also in air masses transported from the open ocean, with a significant anticorrelation between the atmospheric mixing ratios and the height of MABL. We therefore examine how oceanic emissions contribute to the mixing ratios of atmospheric halocarbons taking the height of the marine atmospheric boundary layer (MABL) into account.…”
mentioning
confidence: 72%
“…Samples for dissolved halocarbons in sea water, atmospheric halocarbons and phytoplankton pigments were taken at all 24h-stations in parallel, and additionally four radio sonde launches per 24h-station were accomplished to determine the MABL properties. More details on the campaign and the meteorological conditions can be found in Bange et al (2011) and Fuhlbrügge et al (2013).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations